(untitled) (Cultura Económica, 2021)
On the present essay we present a recapitulation of the debate between C. L. Griswold and I. S. Ross regarding the reasons why Adam Smith was not able to conclude his studies on Natural Jurisprudence. This exchange is appropriate in order to re-examinate Smith’s intellectual project within the so-called Age of Enlightenment. Even though these two authors reach a common place when it comes to the general aims and ends of Smith’s philosophical corpus –and to the fact that it remains incomplete–, they dissent on the reasons of such inconclusion: whereas Griswold alleges a theoretical aporia, Ross arguments that it was Smith’s death what didn’t allow him to conclude his previously announced task. This exercise of recapitulation stands as a point of departure from which we inaugurate future investigations concerning the historical and philosophical roots of Political Economy’s birth, among the Enlightenment philosophical aspirations.